2009
DOI: 10.1166/jnn.2009.m41
|View full text |Cite
|
Sign up to set email alerts
|

Multiscale Study of Hydrogen Diffusion and Clustering on Carbon Nanotube

Abstract: In this paper we report the results of a multiscale study of hydrogen clusterization at the surface of (10,0) carbon nanotube. For this purpose, a systematic study of the binding energies and migration barriers of hydrogen adatom and various close adatom pairs of has been undertaken using density-functional theory approach. The interaction between hydrogen atoms on the surface of nanotube is shown to be long ranged and anisotropic. On applying the obtained potential energy surfaces for lattice kinetic Monte Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 0 publications
1
8
0
Order By: Relevance
“…As we demonstrated earlier, 18 on carbon nanotubes diffusion can efficiently promote hydrogen clustering. However, in the case of nanotubes, the energy barrier for hydrogen diffusion was found to be ∼0.3 eV lower than the energy of hydrogen thermal desorption from the studied nanotube surface (∼1.4 eV 18 ), allowing us to neglect the desorption at temperatures below 500 • C. With graphene, the situation seems to be more complicated.…”
Section: Introductionsupporting
confidence: 63%
See 1 more Smart Citation
“…As we demonstrated earlier, 18 on carbon nanotubes diffusion can efficiently promote hydrogen clustering. However, in the case of nanotubes, the energy barrier for hydrogen diffusion was found to be ∼0.3 eV lower than the energy of hydrogen thermal desorption from the studied nanotube surface (∼1.4 eV 18 ), allowing us to neglect the desorption at temperatures below 500 • C. With graphene, the situation seems to be more complicated.…”
Section: Introductionsupporting
confidence: 63%
“…12,[14][15][16] The effect is similar to that observed for carbon nanotubes, in which hydrogen atoms also introduce isolated levels in the middle of the band gap. 17,18 It has been demonstrated that clustered hydrogen atoms on nanotubes introduce multiple levels in the band gap, 18 which also can be expected for hydrogen clusters on graphene. Thus a proper tuning of nanoisland size and surface coverage patterns opens a way to band gap engineering via hydrogen clustering, either alone 19 or assisted with mechanical deformation, such as deliberate rippling 20 or elastic straining.…”
Section: Introductionmentioning
confidence: 92%
“…In the case of nitrogen it was found that the exact parameterisation of the impurity can affect the quantitative results but that the qualitative behaviour remains the same. The parametrisation of hydrogen used here captures the close range behaviour expected of pairs of hydrogens in graphene and CNTs whereby they prefer to occupy opposite sublattices to each other 25,59,60,68,69 . The aim of this work is to model whether sublattice asymmetry can occur in nanotubes with adsorbed hydrogen impurities, so the behaviour produced by this parameterisation should be sufficient for this purpose.…”
Section: A Tight-binding Model and Inter-impurity Interactionsmentioning
confidence: 99%
“…Although nitrogen doped CNTs are well documented in the literature, hydrogen is an adsorbed impurity, instead of being an sp2 bonded substitutional impurity like nitrogen. The advantages of using hydrogen instead of nitrogen is that the doping can be applied postsynthesis of the graphene sheet and that the adsorbates can migrate atop the graphene with little energy [59][60][61] . This is not the case for nitrogen 14,[62][63][64] , although there is limited evidence to suggest that a subtle version of the sublattice asymmetry effect can be produced using high temperature annealing after post synthesis doping 16 .…”
Section: Introductionmentioning
confidence: 99%
“…Hydrogen clusters are realistic defect candidates because calculations and experiments show that adsorbed hydrogen atoms tend to cluster on SWCNTs' sidewalls. [21][22][23] The rapid development in pattern making, e.g., using block copolymer nanolithography, 24,25 and in fine-tuning and manipulating structures even on the angstrom scale 26 may make regular defect systems feasible and relevant also in the experimental and practical sense.…”
Section: Introductionmentioning
confidence: 99%